Міста Південної Русі: деякі теоретичні проблеми досліджень - Моця, О.П. (Археологія, 2014)
В роботі аналізуються тенденції останніх часів у дослідженні достатньо складної проблеми вітчизняної історії: появи та розвитку урбаністичних центрів на території розселення східних слов’ян (у першу чергу — в її південній частині). Вопросы возникновения и развития урбанистических центров на территории расселения восточных славян в средневековые времена, и в частности в ее южной зоне, привлекают внимание историков и археологов на про тяжении длительного времени. Не стали исключением и разработки последних десятилетий (П.П. Толочко, А.В. Куза и др.). В результате проделанной работы старая формула, а именно, что древнерусский город, в первую очередь, являлся центром ремесла и торговли, была изменена на новую трактовку: город тех времен — это, прежде всего, центр сельскохозяйственной округи, место концентрации, переработки и перераспределения при бавочного продукта (своеобразный коллективный феодальный замок). Но это совершенно не исключает факта наличия в подобных населенных пунктах мощных ремесленных и торговых объединений (просто они не играли роль «первой скрипки» по сравнению с возможностями сельского хозяйства в те времена). В разных регионах Киевской руси и в разное время процесс градообразования имел свои особенности, хотя само урбанизационное направление находилось в пределах общих норм цивилизационного общества тех времен. Issues of urban centres’ foundation and development on the territory of the eastern slavs settling in the mediaeval times, for instance in its southern area, continue to draw the historians’ and archaeologists’ attention already for the long time. the developments of the recent decades are not the exceptions (P.P. tolochko, a.v. kuza, et al.). as a result of the work completed, the old formula considering the ancient rus city first of all as a craft and trade centre was replaced by the new interpretation by which the city of those times was first of all a centre of agricultural region and a place of concentration, treatment and distribution of surplus products, i.e. kind of collective feudal castle. however, it does not exclude the fact of strong craft and trade unions presence in such inhabited localities, they just didn’t played a role of a first fiddle comparing to the opportunities of agriculture in that period. the process of urban building differed with some peculiarities in various regions of kyiv rus and in different time, however, the very urbanization direction extended within the borders of general norms in civilization community of those times.